Land Law Reform in Ensuring Legality and Certainty of Ownership Rights for Houses and Buildings - Ridwan Anthony Taufan; Azis Budianto (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Ownership rights to houses and buildings are the highest form of ownership recognized in the land law system in Indonesia. The legality of this ownership right is vital to ensure legal certainty for the owner and prevent potential disputes that may arise due to unclear ownership status. The study analyzes the legal aspects of ownership rights to houses and buildings, including the legal basis, acquisition procedures, and legal protection mechanisms available to the owner. In addition, this study also examines various problems that often arise in the ownership of property rights, such as overlapping certificates, ownership conflicts, and legal implications in the process of transferring rights. The analysis uses a normative legal method with a conceptual and statutory approach. The Basic Agrarian Law (UUPA), Government Regulations, and Regulations of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (ATR/BPN) are among the regulations that control ownership rights to land and buildings. The statutory approach is carried out by examining these regulations. Meanwhile, the conceptual approach is applied to examine the concept of ownership in land law and the underlying legal principles. The data used in this study are sourced from literature studies, including legal literature, academic journals, and official documents related to land regulations in Indonesia. The results of this study are expected to contribute to a more comprehensive understanding of the legality of ownership rights to houses and buildings, as well as being a reference for landowners, legal practitioners, and the government in managing the legal aspects of land and building ownership. With firmer legal certainty, it is hoped that a more transparent and equitable land system can be created for all interested parties.